1997
DOI: 10.1063/1.363961
|View full text |Cite
|
Sign up to set email alerts
|

Thickness dependence of the switching voltage in all-oxide ferroelectric thin-film capacitors prepared by pulsed laser deposition

Abstract: Thin-film ferroelectric capacitors consisting of PbZr 0.53 Ti 0.47 O 3 sandwiched between La 0.5 Sr 0.5 CoO 3 electrodes have been deposited using pulsed laser deposition. The combination of oxidic perovskite-type materials results in capacitors with a coercive field (E c ) which is comparable with values for bulk ceramics. Textured thin-film capacitors with a columnar microstructure show lower switching voltages than epitaxial films. No thickness dependence of E c and a good endurance up to 10 11 cycles have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
73
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(76 citation statements)
references
References 24 publications
(20 reference statements)
2
73
1
Order By: Relevance
“…Although the measured coercive field was comparable to the theoretical intrinsic value, the authors attributed the large value to substantial enhancments from epitaxial strain and from a conductive nonferroelectric layer 10,13 and, therefore, did not conclude that their results confirmed the observation of intrinsic switching. We found that the coercive field of a vinylidene fluoride-trifluoroethylene copolymer reached the value of the intrinsic coercive field for films with thickess of 15 nm or less, along with the suporting evidence that the temperature dependence agreed very well with mean field theory.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…Although the measured coercive field was comparable to the theoretical intrinsic value, the authors attributed the large value to substantial enhancments from epitaxial strain and from a conductive nonferroelectric layer 10,13 and, therefore, did not conclude that their results confirmed the observation of intrinsic switching. We found that the coercive field of a vinylidene fluoride-trifluoroethylene copolymer reached the value of the intrinsic coercive field for films with thickess of 15 nm or less, along with the suporting evidence that the temperature dependence agreed very well with mean field theory.…”
mentioning
confidence: 67%
“…Landaur estimated this thickness to be of order 1 lm in the case of barium titanate, 7 but experimental studies found that inhomogeneous switching processes continue to dominate in much thinner films. 10 Gerra et al 11 have revised the calculation of critical size for barium titanate and find it to be approximately 10 nm, indicating that homogeneous nucleation should be observable only in ultrathin ferroelectric films.…”
mentioning
confidence: 99%
“…It has been found that the thickness and grain size of the thin film strongly effect the ferroelectric and optical properties, phase transitions, lattice structure, and stress distribution in ABO 3 type materials. [6][7][8][9][10][11][12][13][14][15][16][17][18] Generally speaking, a reduction in film thickness or grain size leads to a decrease in dielectric constant, remanent polarization, dielectric breakdown field, and the tetragonal distortion c/a, and leads to an increase in loss tangent, coercive field, band-gap energy, and diffuseness of the phase transitions. 7,10 Several mechanisms for size effects in ferroelectric thin films have been postulated based on the effects of electrodes/ film interfacial layers, 12-14 stresses, 17 defects, 18 and domain structure transitions.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of space charge and/or depolarizing field at the surface layers 30,31 have been suggested as the cause of the thickness effects. Both of them are attributed to the presence of charge.…”
Section: Resultsmentioning
confidence: 99%